Images of Future Transport in Europe - A study on sustainable mobility : (Policyscenarier för hållbar rörlighet på europanivå) - Dreborg, Karl Henrik (Proceedings from the Annual Transport Conference at Aalborg University, 1998)
The POSSUM project - Policy Scenarios for Sustainable Mobility - is a study funded by the European Commission under the Transport RTD Programme of the 4th Framework Programme. The main task of the POSSUM consortium1 is to construct scenarios for achieving the objectives of sustainable mobility and to assist the Commission in future decisions about the Common Transport Policy (CTP) and the development of the Trans-European Networks (TEN). Thus, based on the EU CTP2 the POSSUM project focuses on the objectives of economic efficiency, regional development and environmental protection. A major element in the concept of sustainable development is preserving the environment and its capability to deliver ecological services to man. Thus sustainability in the POSSUM work has a focus on environmental protection. The end result of the POSSUM project will be a set of scenarios that meet the targets of regional development, efficiency and environmental protection. In this way, European transport policies will be assessed for the first time as to their consistency and feasibility by means of a qualitative scenario approach based on backcasting. This paper depicts Images of the future, that fulfil targets assumed to be in line with CTP.3 The Next step in the work process is to develop scenario paths and policy instruments. This deals with the changes required to reach the different images of the future, and what policy instruments can be utilised to direct the development towards sustainability.